DIAGNOSTIC AND TREATMENT APPROACHES OF ACUTE ADHESION INTESTINAL OBSTRUCTION IN PREGNANT WOMEN AND WOMEN IN LABOR IN THE CONDITIONS OF FULL-SCALE WAR IN UKRAINE - Mishchenko, V.V.; Mishchenko, V.P.; Rudenko, I.V.; Goriachiy, V.V. (World of Medicine and Biology, 2025)
Diagnostic and treatment approaches of acute adhesion intestinal obstruction in pregnant women and women in labor in the conditions of full-scale war in Ukraine. There are changes in the etiopathogenetic mechanisms and clinical features of the course of acute adhesion intestinal obstruction in pregnant women and women in labor as a result of the martial law. 21 pregnant and parturient women with a diagnosis of acute adhesion intestinal obstruction received treatment. An algorithm of treatment and diagnostic approaches to acute adhesion intestinal obstruction in pregnant women and women in labor in modern conditions of full-scale war in Ukraine and negative psycho-emotional impact has been developed. All patients had surgical interventions on the organs of the abdominal cavity in the anamnesis. The psychoemotional state of pregnant women and women in labor was low with acute adhesion intestinal obstruction. The lack of effect of conservative therapy within 2–3 hours was an indication for surgery. Diagnostic and treatment tactics for acute adhesion intestinal obstruction in pregnant women and women giving birth during the martial law in Ukraine should be fast and accurate with the use of additional imaging technologies, standardized depending on the timing, severity of the disease, taking into account the psycho-emotional state of the patients, and should be carried out in compliance with the proposed treatment- diagnostic algorithm.